(untitled) (Research, Society and Development, 2022)
Objective: To describe the lipid distribution profile and the existence of dyslipidemia in market workers in Guanambi/BA. Methods: This was a cross-sectional and census study comprising 399 workers, whose data collection took place between January and March 2018 with the application of a sociodemographic questionnaire, lifestyle, work and health, working and health conditions, and blood lipid testing. Data were tabulated and analyzed using Epi Info version 7.0. Results: It was found that 313 (78.5%) stallholders had some type of dyslipidemia, 144 workers (36.1%) had elevated TG, 272 (68.7%) had reduced HDL-C and 54 (14.1 %) increase in LDL-C. With regard to the elevation of LDL and TG in the same individual, 22 (5.8%) marketers registered an increase in both. Most workers were female (n= 241; 66.4%).Market vendors who work more than 44 hours a week had a higher frequency of dyslipidemia (n=174; 59.6%).Conclusion: Given the above, it is emphasized the importance of carrying out educational activities in the environment of the open market in Guanambi, as well as improvements in the infrastructure of the space so that marketers can carry out their work activities safely.